The Effect of Endorphin Massage on the Sleep Quality of Third-Trimester Pregnant Women - Dwi Estuning Rahayu; Az Zahra Nafahati Shafa; Chelsia Rahma Adinda; Choirun Nisak Jayanti; Dea Oktavia Rahmadhani (KHD Production, 2025)
Sleep disturbances are common among pregnant women, especially in the third trimester, but effective non-pharmacological interventions are still limited. This study aims to analyze the effect of endorphin massage on the sleep quality of pregnant women aged 37–40 weeks. The study design used a pre-experimental one-group pretest–posttest without a control group. A total of 30 respondents were selected through total sampling. Endorphin massage was administered twice, with each session lasting 15–20 minutes. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). The results showed a change in the PSQI score from a pretest average of 9.3 to 7.8 on the posttest; however, the McNemar test produced a p-value of 1.00 (p > 0.05), indicating that there was no statistically significant effect. Clinically, endorphin massage has the potential to enhance sleep quality through its relaxation and endorphin release mechanisms. This study concludes that although not statistically significant, endorphin massage may be considered as a supportive therapy to enhance sleep comfort in pregnant women. Limitations of this study include a small sample size and the absence of a control group; thus, further research with a stronger design is needed.